Drug courts in theory and in practice - Nolan, James L. Jr. (Social problems and social issues, 2002)
Baltimore City Drug Court : transforming the traditional adversarial model / William D. McColl -- Systemic constraints on the implementation of a Northeastern drug court / Elaine M. Wolf -- West coast drug courts : getting clients morally involved in the criminal justice process / Sara Steen -- The Denver Drug Court and its unintended consequences / Morris B. Hoffman -- Separated by an un-common law : drug courts in Great Britain and America / James L. Nolan, Jr. -- The adversary system and the attorney role in the drug court movement / Richard C. Boldt -- Therapeutic jurisprudence and drug treatment courts : integrating law and science / Peggy F. Hora and John Terrence A. Rosenthal -- Drug treatment courts : a traditional perspective / Susan Meld Shell -- The drug court movement : an analysis of tacit assumptions / James J. Chriss -- Drug control and the ascendancy of Britain's therapeutic culture / Frank Furedi -- Drug courts, the judicial role, and the rehabilitative ideal / Philip Bean.